The Role of Twitter to The Babarsari Riot on Yogyakarta People’s Stereotype of Eastern Indonesian - Gusti Panji (Jogjakarta Communication Conference (JCC), 2023)
The outbreak of riots between Maluku and East Nusa Tenggara communities in Babarsari, Sleman on 2 July 2022 became a topic of conversation on social media Twitter. It also made the news media spread information about the incident. This research uses a qualitative approach to determine the relationship between the people of Yogyakarta and Eastern Indonesians, the effect of the Babarsari riots on the stereotype of the people of Yogyakarta on the people of Eastern Indonesia and the impact, both on the people of eastern Indonesia itself and the Yogyakarta people. The data collection techniques used in this research are literature review and interview.